2020
DOI: 10.1038/s41598-020-73723-8
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic footprint of compromised insulin sensitivity under fasting and hyperinsulinemic-euglycemic clamp conditions in an Arab population

Abstract: Metabolic pathways that are corrupted at early stages of insulin resistance (IR) remain elusive. This study investigates changes in body metabolism in clinically healthy and otherwise asymptomatic subjects that may become apparent already under compromised insulin sensitivity (IS) and prior to IR. 47 clinically healthy Arab male subjects with a broad range of IS, determined by hyperinsulinemic-euglycemic clamp (HIEC), were investigated. Untargeted metabolomics and complex lipidomics were conducted on serum sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…Diabetes-specific alterations of protein and metabolite levels have previously been described in different populations [42][43][44][45] . To validate the metabolomic and proteomic data in QBB and its ability to characterize T2D participants, we investigated omics-associations with T2D.…”
Section: Resultsmentioning
confidence: 93%
“…Diabetes-specific alterations of protein and metabolite levels have previously been described in different populations [42][43][44][45] . To validate the metabolomic and proteomic data in QBB and its ability to characterize T2D participants, we investigated omics-associations with T2D.…”
Section: Resultsmentioning
confidence: 93%
“…The study subjects were selected from among a cohort of 60 subjects previously described [ 20 , 21 ]. The subjects were young adult, normoglycemic (normal fasting glucose and normal response to 75 g oral glucose tolerance test), healthy (no medication and no chronic diseases), and with body mass index below 28.…”
Section: Methodsmentioning
confidence: 99%
“…We have recently reported that insulin sensitivity, measured by HIEC, varied widely among euglycemic young healthy men (15) and correlated with circulating metabolomic signatures (16). The goal of the present study was to evaluate the altered expression pattern of skeletal muscle proteins associated with reduced insulin sensitivity in muscle biopsies taken at the basal state and during insulin infusion, at the end of the insulin clamp, when both glycemia and glucose infusion have stabilized.…”
Section: Introductionmentioning
confidence: 93%
“…As previously reported (16), the subjects were admitted to the research study unit at 7 a.m., after 10-12 h of overnight fasting, and a baseline muscle biopsy was obtained before the clamp study. Three polyethylene catheters were inserted in the antecubital fossa and back of the hand veins, enabling insulin/ dextrose infusions, blood glucose measurements, and blood sampling.…”
Section: Hyperinsulinemic Euglycemic Clampmentioning
confidence: 99%
See 1 more Smart Citation